Perceptions of factors affecting the pursuit of higher education among disadvantaged grade 12 learners. - Ebrahim, Tasneem (My University, 2010)
Prior to 1994, education in South Africa was formally and legally segregated according to race and ethnicity. The pre-eminent transformation demand for the educational policies of the post-1994 democratic government was therefore to promote equity in enrolments and staffing across educational sectors, so that equal opportunities can exist for the broader society. Fifteen years after democracy the expectation is that diversity and inclusivity would not be in question. However, it appears that access and participation in higher education still remains reserved for a small elite. Policy gains have therefore been modest. This study attempts to understand the reasons for the slow transformation in equity gains in higher education by interviewing disadvantaged Grade 12 learners in a school south of Johannesburg. The qualitative approach using a semi-structured questionnaire was utilized to facilitate a dialogue about their perceptions of what prevents these learners from accessing higher education. Thematic content analysis of the participants’ responses revealed four salient themes: perceptions of the economic, educational, socio-cultural and political constraints to higher education which are discussed using Paulo Freire’s theory of conscientisation as a conceptual framework. The results of this research imply that a broader more purposeful approach to social reform and more comprehensive and equitable strategies of redistribution of wealth and income are required to empower disadvantaged communities to access higher learning institutions in South Africa.